Habitat selection by Mottled Duck Anas fulvigula broods - Krainyk, Anastasia; Finger, Richard S.; Ballard, Bart M.; Merendino, M. Todd; Wester, David B.; Terry, Russel H. (Wildfowl, 2018)
The western coast of the Gulf of Mexico provides important habitat for migrating and resident waterfowl, including the Mottled Duck Anas fulvigula, which relies on this region for all of its life-cycle events. The Western Gulf Coast (WGC) population has been in decline since the 1970s, primarily because of loss and degradation of large tracts of wetlands and coastal prairies due to human activities. The Mottled Duck Conservation Plan, developed by academics involved in Mottled Duck research, state and federal biologists, U.S. Fish and Wildlife Service migratory bird staff, flyway council representatives, and others, suggested that increasing recruitment is essential for the recovery of the population. Management and preservation of brood-rearing habitats are crucial for increasing recruitment rates. However, gaps still exist in knowledge of the species’ ecological requirements, and relatively little research has been conducted on wetland habitat selection by female Mottled Ducks with broods. This study investigated habitat selection by 82 Mottled Duck broods from six replicate surveys of 300 wetlands in 1994 and 330 wetlands in 1995 along the Texas coast, and by tracking the movements of 14 radio-marked Mottled Duck females with broods in 2001. Brood-rearing Mottled Ducks selected palustrine unconsolidated bottom, palustrine aquatic bed, palustrine emergent, and estuarine intertidal aquatic bed wetlands. The average distance between the nest site and the wetland first used by Mottled Duck broods was 1,073 m, and the median longest daily movement by female Mottled Ducks throughout the brood-rearing period was 1,497 m. These results indicate that the proximity of nesting habitat to brood-rearing habitat is an important landscape variable to consider for future management strategies. Brood survival is a major factor driving Mottled Duck recruitment; creating or managing wetlands for these key characteristics therefore may help increase recruitment rates and stabilise the WGC Mottled Duck population.